Delivering on the Promise of Pro-Poor Growth : Insights and Lessons from Country Experiences - Besley, Timothy (Washington, DC: World Bank and Palgrave Macmillan, 2012)
Delivering on the Promise of Pro-Poor Growth contributes to the debate on how to accelerate poverty reduction by providing insights from eight countries that have been relatively successful in delivering pro-poor growth: Bangladesh, Brazil, Ghana, India, Indonesia, Tunisia, Uganda, and Vietnam. It integrates growth analytics with the microanalysis of household data to determine how country policies and conditions interact to reduce poverty and to spread the benefits of growth across different income groups. This title is a useful resource for policy makers, donor agencies, academics, think tanks, and government officials seeking a practical framework to improve country level diagnostics of growth-poverty linkages.